The secret keepers of Old Depot Grocery - Cox, Amanda, 1984- (Revell, a division of Baker Publishing Group, 2021)
"For decades, three generations of women of Old Depot Grocery have been keeping secrets from each other. When Sarah returns home with hopes of running the store, the long-buried past will be brought into the light and threaten not only to destroy the family business but sever the family ties"--